Review pathway analysis for peptide‐mediated electronic coupling in the super‐exchange mechanism of ET and EET1. Issue 1 (19th January 2013) - Kawatsu, Tsutomu; Maran, Flavio; Toniolo, Claudio
Abstract Electron and excitation energy transfers (ET and EET) have an important role in biological energy‐exchange processes. Proteins are an inhomogeneous and anisotropic medium for ET and EET. The protein structure influences electronic coupling, an important factor for ET and EET. The structure factor may be predicted by obtaining information about the tunneling pathways. The present paper mainly focuses on tunneling pathway analysis using the tunneling current (flux) of the electron or configuration density. The tunneling pathways for ET and singlet EET through peptides are introduced using tunneling current (flux) analysis. These tunneling pathways differ greatly between ET and singlet EET. This paper also reviews both the theoretical background and other methods for determining electronic tunneling pathways. These pathways are related to the effect of protein coordinates on the electronic coupling between the initial and final states of the ET and EET. © 2012 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 100–113, 2013.